# Solve the system 7x + 2y = 12 x - 3y = 5

### 2 Answers | Add Yours

We'll use substitution method for solving the system. We'll note the equations of the system as:

7x + 2y = 12 (1)

x - 3y = 5 (2)

We'll isolate x in the second eq.:

x = 3y+5 (3)

We'll substitute (3) into (1):

7(3y+5) + 2y = 12

We'll remove the brackets:

21y + 35 + 2y - 12 = 0

We'll combine like terms:

23y + 23 = 0

We'll factorize:

23 (y+1) = 0

We'll divide by 23:

y+1 = 0

**y = -1**

We'll substitute y in (3):

x = 3y+5

x = -3 + 5

**x = 2**

**The solution of the system is {(2,-1)}.**

7x + 2y = 12 ....(1)

x-3y = 5 ............(2)

Using the substotitution method

rewrite (2):

==> x= 3y + 5

Now substotitute in (1):

7x + 2y = 12

7(3y+5) + 2y = 12

21y + 35 = 2y = 12

23y = -23

==> y= -23/23= 1

==> **y= 1**

Now to calculate x:

x= 3y + 5

= 3(1) +5 = 8

==> **x= 8**